2 | ( | X | + | 3 | ) | − | 5 | + | 5 | X | = | 3 | ( | X | − | 1 | ) |
Left side of the equation = | 2 | X | + | 2 | × | 3 | − | 5 | + | 5 | X |
= | 2 | X | + | 6 | − | 5 | + | 5 | X |
= | 7 | X | + | 1 |
7 | X | + | 1 | = | 3 | ( | X | − | 1 | ) |
Right side of the equation = | 3 | X | − | 3 | × | 1 |
= | 3 | X | − | 3 |
7 | X | + | 1 | = | 3 | X | − | 3 |
7 | X | − | 3 | X | = | - | 3 | − | 1 |
4 | X | = | - | 3 | − | 1 |
4 | X | = | - | 4 |
X | = | - | 4 | ÷ | 4 |
= | - | 4 | × | 1 4 |
= | - | 1 | × | 1 |
X | = | - | 1 |